Prediksi Harga Kontrak Opsi Asia dalam Perdagangan Pasar Saham dengan Menggunakan Metode Monte Carlo - Rahmat Syam; Ahmad Zaki; Muhammad Hasriyadi Basri (Journal of Mathematics, Computations and Statistics, 2018)
Option is a contract that gives rights (not obligations) to the contract holder (option buyer) to buy or sell a certain asset of a company to the option writer (option writer). Monte Carlo is a method that requires a simulation model that includes random numbers and samples based on computers. The simulation procedure involves generating random numbers by providing a probability density and using the law of large numbers to get the average of its values as an estimator of the expected value of the random variable. This study aims to predict stock option prices in the future and as a material consideration for stock trading players to make a decision to sell or buy options for a stock using Matlab software. The type of research used is applied research using the Monte Carlo method to simulate stock data. The results show that the more iterations are carried out, the predictive value is also getting better and converging to a value. The predictive value is stable at the 60000th iteration with an error value of MAPE of less than 20% so that the predicted value can be said to be good.